An Application to Latin America of a Dual Synergies Model: Can a New Industrial Policy Break the Middle Income Trap? - Santosh Mehrotra (Institute of Labor Economics (IZA), 2025)
The paper applies the "dual synergies" model—linking economic growth, poverty reduction, and human capability formation—to explain why Latin America (LAC) remains trapped at middle-income levels. It challenges orthodox views that prioritize growth alone, arguing instead that growth, social policy, and human capital mutually reinforce each other. Using stylized facts, the paper shows that LAC's extractive, commodity-dependent development model has produced volatile growth, weak job creation, high informality, and limited poverty reduction. This contrasts sharply with East Asia, where coordinated industrial policy, early investments in health and education, and financial deepening enabled sustained growth and structural transformation. In LAC, weak fiscal capacity, low savings, foreign-dominated banking, and inequality constrain public investment in human capital, weakening growth–poverty links. The paper argues that breaking the middle-income trap requires an integrated strategy: a renewed, state-capable industrial policy aimed at diversification, innovation, and manufacturing upgrading, combined with stronger social policies.
Keywords: O11; O14; O15; O25; 330; Latin America; industrial policy; East Asia